The Gingiva of Horses With Pituitary Pars Intermedia Dysfunction: A Macroscopic Anatomical Evaluation - Nitzsche, Anne Maria; Fey, Kerstin; Büttner, Kathrin; Gröf, Manuela; Staszyk, Carsten (Frontiers in Veterinary Science, 2022)
Pituitary pars intermedia dysfunction (PPID) is a common neurodegenerative disease mainly in horses older than 15 years. The domestic equine population is following the same demographic change as that seen in humans; it is aging and veterinarians are asked to attend to geriatric horses more frequently. Common problems seen regularly in older equines are dental disorders and especially periodontal disease. As a systemic and endocrine disease, associated with delayed wound healing and impaired immune function, PPID should be considered before major dental treatment in aged equines is started. Possible negative effects of PPID on epithelial tissues could also affect the periodontium. Therefore, the aim of the present study was to identify gross changes in the gingiva associated with PPID. Fourteen horses with clinical signs of PPID and adenoma in the pituitary pars intermedia and 13 controls showing neither clinical signs nor PPID-associated histological changes in the pituitary gland were included. PPID-affected horses (26.9 ± 0.73 years) were significantly older than controls (20.0 ± 1.24 years). In the PPID-affected group, significantly more often an irregular and bulky appearance of the gingival texture was observed, as well as an irregular shape of the gingival margin. Furthermore, the sulcus gingivalis of cheek teeth frequently was deeper than 1 mm. These findings indicate a possible association between age, soft tissue alterations, and PPID and suggest a potential predisposition of PPID-affected horses for periodontal diseases.